2022
DOI: 10.3390/ijerph191811288
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships between Children’s Oral Health and Parents’ Oral Health Knowledge, Literacy, Behaviours and Adherence to Recommendations: A Cross-Sectional Survey

Abstract: Although preventable, early childhood caries (ECC) is a burdening condition in all WHO regions, with Poland being one of the most affected countries in Europe. Effective home-based prevention of ECC is available and recommended by several expert bodies. Therefore, we wanted to determine how well parents were following selected oral health recommendations in preschool children. Additionally, we wanted to determine which socioeconomic factors influenced such practices the most, and how parents’ oral health liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Dental caries has been reported to affect 60%-90% of school-age children (Tham et al, 2015). It is widely known that caries and its complications can seriously affect general health and quality of life, and studies have shown that social determinants of health are important in the prevention of dental caries (Chawłowska et al, 2022). These social determinants include family income, parents' education, place of residence, mother's age, number of children in the family, parents' oral hygiene practices and parents' oral health status (Chawłowska et al, 2022) , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries has been reported to affect 60%-90% of school-age children (Tham et al, 2015). It is widely known that caries and its complications can seriously affect general health and quality of life, and studies have shown that social determinants of health are important in the prevention of dental caries (Chawłowska et al, 2022). These social determinants include family income, parents' education, place of residence, mother's age, number of children in the family, parents' oral hygiene practices and parents' oral health status (Chawłowska et al, 2022) , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that caries and its complications can seriously affect general health and quality of life, and studies have shown that social determinants of health are important in the prevention of dental caries (Chawłowska et al, 2022). These social determinants include family income, parents' education, place of residence, mother's age, number of children in the family, parents' oral hygiene practices and parents' oral health status (Chawłowska et al, 2022). According to the Turkey Oral and Dental Health Profile Research Report, 34.5% of children in the 5‐year age group and 38.8% of children in the 12‐year age group have experienced toothache or dental‐related discomfort in the last year (Tezel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Parents play a pivotal role in deciding treatment approaches and how these treatments are administered [ 18 ]. Concurrently, a child's perceptions about oral health are greatly influenced by parental words and actions [ 19 ]. Dentists, in ensuring successful treatments, utilize various methods to manage children's behavior during dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intranasal sedation is contraindicated in cases of hypersensitivity reactions, otorhinolaryngeal conditions such as rhinitis or nasal polyposis, respiratory diseases, cardiac diseases, and upper respiratory tract infections. Additionally, recent administration of nasal vasoconstrictors may reduce the absorption of intranasally administered medications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 12 ] Also, when it comes to parents, there is an association between how parents rate the status of the oral cavity and the severity of their children’s oral health condition. [ 13 ] Understanding what good oral health means can differ from one parent to another. [ 12 14 , 15 ] Previous studies have shown variability in how parents rate their children’s oral health and how the children would rate their own oral health.…”
Section: Introductionmentioning
confidence: 99%